Crucial role of carbonic anhydrase IX in tumorigenicity of xenotransplanted adult T‐cell leukemia‐derived cells. Issue 3 (March 2017) - Nasu, Kentaro; Yamaguchi, Kazunori; Takanashi, Tomoka; Tamai, Keiichi; Sato, Ikuro; Ine, Shoji; Sasaki, Osamu; Satoh, Kennichi; Tanaka, Nobuyuki; Tanaka, Yuetsu; Fukushima, Takuya; Harigae, Hideo; et al.
Abstract : Carbonic anhydrase IX (CA9) is a membrane‐associated carbonic anhydrase that regulates cellular pH, is upregulated in various solid tumors, and is considered to be a therapeutic target. Here, we describe the essential role of CA9 in the tumorigenicity of cells derived from human adult T‐cell leukemia/lymphoma (ATL). We previously established the highly tumorigenic ST1‐N6 subline from the ATL‐derived ST1 cell line by serial xenotransplantation in NOG mice. In the present study, we first show that CA9 expression is strongly enhanced in ST1‐N6 cells. We then sorted ST1 cells by high or low CA9 expression and established ST1‐CA9 high and ST1‐CA9 low sublines. ST1‐CA9 high cells, like ST1‐N6 cells, were more strongly tumorigenic than ST1‐CA9 low or parental ST1 cells when injected into NOG mice. Knockdown of CA9 with shRNAs suppressed the ability of ST1‐CA9 high cells to initiate tumors, and the tumorigenicity of ST1 cells was significantly enhanced by introducing wild‐type CA9 or a CA9 mutant with deletion of an intracytoplasmic domain. However, a CA9 with point mutations in the catalytic site did not increase the tumorigenicity of ST1 cells. Furthermore, we detected a small population of CA9 + CD25 + cells in lymph nodes of ATL patients. These findings suggest that CA9, and particularly its carbonic anhydrase activity, promotes the tumorigenicity of ATL‐derived cells and may be involved in malignant development of lymphoma‐type ATL. Abstract : Carbonic anhydrase 9 plays a crucial role in tumor formation of ATL‐derived ST1 cells when xenotransplanted into immunodeficient NOG mice. This enzyme is also expressed in lymphoid tissues of ATL patients.